Battles of history and memory. A first general mapping of conceptions and proposals from Latin America and Europe - Barria-Asenjo, Nicol A.; Camargo-Castillo, Javier; Maiwald, Florian; Salas, Gonzalo; Ayala-Colqui, Jesús; Vergara Muñoz, Francisco Alejandro (Perseitas, 2025)
In this article we find a general mapping of diverse conceptions and fundamental notions to think the wide spectrum of history, historicity, historical time among other essential elements for our contemporaneity. Current politics, eclipsed by struggles and conceptual battles and their abstraction, requires attentive analysis of the historical movements of the present. Taking memory and history through a political lens, then, forces us to dispute the construction of the social order installed at a given social time. The objective of this paper is, first, to discuss how it is possible to conceive of memory and the emergence of novelty, particularly by delving into the ideas of Horkheimer and Arendt –since in her work as well, through the notion of “natality”, memory becomes less an act of preservation and more an exercise of judgment, distinction, and action, which allows us to connect with the theme of political struggles over memory. This will enable us to situate the state of memory in terms of Europe. Subsequently, we aim to contrast this perspective and ground it in Latin America, where many countries have been victims of systematic human rights violations. These two scenarios are considered with the purpose of contrasting some particular conflicts and perspectives that are relevant to global dilemmas.